International Criminal Law I: The History of International Criminal Law - Škulić , Milan (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This text outlines the basic features of the history and development of international criminal law and international criminal justice, with a special emphasis on the establishment of the permanent International Criminal Court, which the author treats as a new beginning rather than the end of the development of international criminal justice. The author also provides an overview of the history of international criminal justice, closely associated with the general history of civilisation and military history.The author includes some selected and significant moments for the development of the international criminal law: 1) the trial in Breisach of the Duke of Burgundy, Sir Peter von Hagenbach, in 1474, in the context of the juvenile stage of international criminal justice; 2) the idea of an international war crimes court, unrestrained by state borders, articulated after the war between Prussia and France; 3) the attempt at trying the former German emperor, Leipzig war crimes trials and parallel proceedings in France and Belgium after the WWI; 4) the activities of some international organisations between WWI and WWII and an unsuccessful attempt at establishing an international criminal court against terrorism; 5) the Nuremberg (IMT) and Tokyo Trials (IMTFE) after the WWII, with an explanation that the principles developed by the International Military Tribunal in Nuremberg represent an extremely important basis for the further development of international criminal law and that criminal law applied at Nuremberg formally became the backbone of international criminal law; 6) the establishment of the ad hoc tribunals for the former Yugoslavia (ICTY) and Rwanda (ICTR); 7) the hybrid tribunals, with combination of national and international elements and 8) the perspectives of the International Criminal Law after the adoption of the Rome Statute and establishment of a permanent international criminal court (ICC). The author concludes that, when it comes to the future of the International Criminal Court, one should be neither an optimist nor a pessimist, as for what lies ahead of the first permanent form of international criminal justice, the old truth holds that a glass half filled with water may be seen as either half-full or half-empty.Keywords: history, international criminal law, international military tribunals at Nuremberg (IMT) and Tokyo (IMTFE), international criminal tribunals for the former Yugoslavia (ICTY) and Rwanda (ICTR), permanent international criminal court (ICC)